A questão portuária e o desenvolvimento regional: análise da infraestrutura do Porto de Salvador (Ba) e os seus reflexos para o comércio exterior baiano - SANTOS, Darlã Conceição (2016)
The port system is a strategic element for regional development. The improvement in logistics infrastructure of ports, provides the rise of Brazil's relations with the world, as most traded goods pass through ports. Even so, the country needs a more agressive investment policy and more efficient infrastructure in order to stimulate the flow and movement of import and export operations. This will help reduce the costs associated to logistics that are passed on the to business using these services. In addition to this, an imprpved infrastructure will optimize time and increase the competitiveness of Brazil in the global market. This study aims to analyze the logistics infrastructure of the Port of Salvador (BA) and its main impacts on external trade performance of Bahia. It presents the historical background of the Port of Salvador, since its inception to the present day. The research, in addressing the problem, is classified as qualitative and quantitative, in techniques of literature, documentary and field research were used. Some concepts of ports, their functions, physical elements and their importance in local, regional and national development have been highlighted through bibliographical and documentary research and present key regulatory frameworks of the national port system. In addition to this analysis, the study also reviews the literature on ports and foreign trade, has some international and regional port models, such as Shanghai, Singapore, Rotterdam, Suape, Pecém and Itaqui. In the field of research, the study reveals the vision of 100 major companies that operate with the flow of goods through the Port of Salvador, highlighting the critical points for performance excellence. Questionnaires was applied to business leaders with extensive experience in the port and foreign trade, and the results revealed amazing insights, such as the need for an additional port in the state of Bahia to divide operations with the Port of Salvador, especially the growing annual increase in the foreign trade cargo flow, which have outpaced the investments and improvements in port infrastructure